2011
DOI: 10.1590/s0103-51502011000100018
|View full text |Cite
|
Sign up to set email alerts
|

Diferenças biomecânicas entre os gêneros e sua importância nas lesões do joelho

Abstract: INTRODUÇÃO: Diversas pesquisas têm sido realizadas para determinar os fatores biomecânicos responsáveis pela maior incidência da síndrome da dor femoropatelar e das lesões do ligamento cruzado anterior em mulheres quando comparadas aos homens. OBJETIVO: O objetivo deste estudo foi realizar uma revisão de literatura não sistemática das diferenças biomecânicas entre os gêneros, especialmente aquelas referentes à articulação do quadril, potencialmente responsáveis pela maior incidência de lesões no joelho em mulh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 37 publications
(45 reference statements)
0
7
0
7
Order By: Relevance
“…O presente estudo realizou a investigação apenas no sexo feminino já que de acordo com Baldon et al (2011), as mulheres atletas apresentarem maior incidência de SDPF quando comparadas aos homens, o que pode ser causado por fatores anatômicos, como o desequilíbrio muscular e o desalinhamento do membro inferior, fatores neuromusculares, fatores hormonais além de maior frouxidão do joelho (VORA et al, 2017). Sabe-se que as mulheres apresentam maior valor do ângulo Q, devido à largura da pelve ser maior no sexo feminino (KODAMA et al, 2017) Este aspecto da anatomia pode alterar o padrão de movimento do membro inferior durante a corrida.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…O presente estudo realizou a investigação apenas no sexo feminino já que de acordo com Baldon et al (2011), as mulheres atletas apresentarem maior incidência de SDPF quando comparadas aos homens, o que pode ser causado por fatores anatômicos, como o desequilíbrio muscular e o desalinhamento do membro inferior, fatores neuromusculares, fatores hormonais além de maior frouxidão do joelho (VORA et al, 2017). Sabe-se que as mulheres apresentam maior valor do ângulo Q, devido à largura da pelve ser maior no sexo feminino (KODAMA et al, 2017) Este aspecto da anatomia pode alterar o padrão de movimento do membro inferior durante a corrida.…”
Section: Discussionunclassified
“…Sabe-se que as mulheres apresentam maior valor do ângulo Q, devido à largura da pelve ser maior no sexo feminino (KODAMA et al, 2017) Este aspecto da anatomia pode alterar o padrão de movimento do membro inferior durante a corrida. Baldon et al (2011) (HUBERTI;HAYES, 1984).…”
Section: Discussionunclassified
“…Still emphasizing the difference between genders analyzed in the present study, many studies in the literature that evaluate different sports movements such as running, walking, and changing direction also report greater dynamic valgus among women. 19 Therefore it is suggested that the difference between genders in the angles in valgus of the knee during sports maneuvers, as well as in the postures adopted by women before landing on the ground, is the consequence of an altered muscle control of the lower limb and probably reflects differences in the contraction pattern of the periarticular muscles of the knee, as well as of the hip muscles, contributing to the disparity of injuries between genders, which may justify any difference that may have occurred in the results. [19][20][21] Although the present study did not evaluate postural changes, in case alterations in the RMS values were found between genders, these could be explained by the studies mentioned above.…”
Section: According To Teixeiramentioning
confidence: 99%
“…Between the factors that predispose to the lesions in this joint, we highlight the dynamic valgus, which is characterized by the misalignment of the lower limb in the frontal plane, caused by the adduction and medial rotation of the hip, being directly influenced by the body structure and the stabilizing inability of the external rotator muscles of the hip, specifically the gluteus medius, in the performance of functional movement patterns [7][8][9] . Females presented biomechanical differences in lower limb movement pattern when compared to men, due to anatomical and physiological factors, such as wider pelvis, delayed activation of the medial musculature of the knee, lower joint stiffness and body mass, contributing to a higher incidence of valgus observed in this gender 10 .…”
Section: Introductionmentioning
confidence: 96%